Inhibition of the notch signaling pathway overcomes resistance of cervical cancer cells to paclitaxel through retardation of the epithelial–mesenchymal transition process. Issue 9 (28th May 2021) - Sun, Tianzhu; Zhang, Dengyang; Wang, Zehao; Zhao, Bingyu; Li, Yaping; Sun, Xiuli; Liu, Jia; Wang, Xuanjun; Sheng, Jun
Abstract: Use of paclitaxel as monotherapy or in combination with other therapeutic agents is a widely employed front‐line chemotherapeutic strategy for cervical cancer. However, previous reports have shown that approximately 70% of the patients with cervical cancer develop resistance to paclitaxel. Epithelial–mesenchymal transition (EMT) contributes to the occurrence of chemoresistance in several types of cancer, including cervical cancer. Identification of the critical signaling pathway that regulates the EMT process may provide a novel strategy for avoiding or delaying the emergence of paclitaxel resistance during the treatment of cervical cancer. Herein, we established a paclitaxel‐resistant cervical cancer cell line (HeLa‐229PTR cells) by culturing parental HeLa‐229 cells with increasing concentrations of paclitaxel. We observed elevated expression of Notch1 in HeLa‐229PTR cells compared with their parental HeLa‐229 cells, indicating its potential involvement in the EMT phenotype of the paclitaxel‐resistant cells. Furthermore, silencing of the NOTCH1 gene, as well as treatment with a γ‐secretase inhibitor (DAPT) partially reversed the EMT phenotype and significantly enhanced the sensitivity of HeLa‐229PTR cells to paclitaxel. Moreover, we found that DAPT could significantly inhibit invasiveness, reduce colony formation activity, and promote apoptosis of HeLa‐229PTR cells. Taken together, these results indicated that HeLa‐229PTR cells develop the EMT phenotype partly through activation of Notch1 signaling. Thus, inhibition of Notch1 signaling can be a strategy for the reversal of the EMT phenotype and may increase the sensitivity of cervical cancer cells to treatment with paclitaxel. Abstract :